2008
DOI: 10.1038/sj.bjc.6604508
|View full text |Cite
|
Sign up to set email alerts
|

VEGF expression by mesenchymal stem cells contributes to angiogenesis in pancreatic carcinoma

Abstract: Little is known about the factors that enable the mobilisation of human mesenchymal stem cells (MSC) from the bone marrow into the blood stream and their recruitment to and retention in the tumour. We found specific migration of MSC towards growth factors present in pancreatic tumours, such as PDGF, EGF, VEGF and specific inhibitors Glivec, Erbitux and Avastin interfered with migration. Within a few hours, MSC migrated into spheroids consisting of pancreatic cancer cells, fibroblasts and endothelial cells as m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
258
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 359 publications
(275 citation statements)
references
References 40 publications
9
258
0
8
Order By: Relevance
“…34,35 A variety of studies revealed that both, the scaffold material, 6 as well as scaffold-bound cells have their own, discrete bioactive properties, which may influence the scaffold/tissue interaction, respectively. 28,35,36 Bioactive glasses, as reviewed by Hoppe et al, 6 are known to release various ion products. The ion dissolution products of 45S5 Bioglass Ò , are presumed to comprise Si, Ca, Na, and P. 6 The subsequent release of these ions after exposure to a physiological environment is then believed to favorably affect the behavior of human cells and to enhance the bioactivity of the scaffolds related to both osteogenesis and angiogenesis.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…34,35 A variety of studies revealed that both, the scaffold material, 6 as well as scaffold-bound cells have their own, discrete bioactive properties, which may influence the scaffold/tissue interaction, respectively. 28,35,36 Bioactive glasses, as reviewed by Hoppe et al, 6 are known to release various ion products. The ion dissolution products of 45S5 Bioglass Ò , are presumed to comprise Si, Ca, Na, and P. 6 The subsequent release of these ions after exposure to a physiological environment is then believed to favorably affect the behavior of human cells and to enhance the bioactivity of the scaffolds related to both osteogenesis and angiogenesis.…”
mentioning
confidence: 99%
“…This approach bears the chance that the cells constantly secrete capillary recruiting mediators [27][28][29] and therefore, induce long-term vessel growth. To biofunctionalize scaffolds, high numbers of adult progenitor cells can easily be isolated, for example, from human adipose tissuederived stem cells (hASC), but they are present and responsible for tissue repair and tissue regeneration in every adult tissue.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Other pro-tumorigenic effects of MSCs in tumour stroma include promotion of angiogenesis via differentiation to mural cells or pericytes, or the secretion of vascular endothelial growth factor [22][23][24]. MSCs in the tumour stroma were also found to regulate immune system function, with an overall immunosuppressive effect.…”
Section: The Role Of Mscs In Cancer Development and Progressionmentioning
confidence: 99%
“…These growth factors attract MSCs across a Boyden chamber membrane without further stimulus being required, can act synergistically with cytokines and have their pro-migratory effect blocked by antibodies or specific inhibitors [24,[37][38][39][40]. In an intracranial mouse model of glioma, low PDGF-BB-expressing U87 cells attracted fewer MSCs and grew to a smaller size than high expressing clones [39].…”
Section: How Are Mscs Attracted To the Tumour Site?mentioning
confidence: 99%